Exploratory The Transitional Impact From Lean Production To Open Source - Puvanasvaran, A. Perumal; Al Amin, Mohamed Sultan; Mohd Syaiful Rizal, Abdul Hamid; Norazlin, Nasir (Asianet-Pakistan, 2014)
Lean production and open source innovation are the two forces that drive business success today. However, some aspects of lean production may adversely affect a company’s capability to be successful with open source innovations. This study aims to examine open source adoption in the government and private sectors, and to identify the factors and challenges involved in its adoption. Lean production and open source innovation are related because their application can be integrated, considering the similarity in their operational purposes such as cost reduction and expediting processes. With good communication levels, lean production and open source innovation can achieve and encourage innovation capabilities (continuous improvement) in the organization. Although more than 50% of the respondents agreed that open source provides several benefits to their organization, they do not deny the challenges that come with service adoption. Finally, this study discusses the transitional effect of open source innovation.